Sirtuin-6 Preserves R-spondin-1 Expression and increases Resistance of intestinal Epithelium to injury in Mice - Fangyi Liu; Heng-Fu Bu; Hua Geng; Isabelle G. De Plaen; Chao Gao; Peng Wang; Xiao Wang; Jacob A. Kurowski; Hong Yang; Jiaming Qian; Xiao-Di Tan (BMC, 2017)
Abstract Sirtuin-6 (Sirt6) is a critical epigenetic regulator, but its function in the gut is unknown. Here, we studied the role of intestinal epithelial Sirt6 in colitis-associated intestinal epithelial injury. We found that Sirt6, which is predominantly expressed in epithelial cells in intestinal crypts, is decreased in colitis in both mice and humans. Colitis-derived inflammatory mediators including interferon-γ and reactive oxygen species strongly inhibited Sirt6 protein expression in young adult mouse colonocyte (YAMC) cells. The susceptibility of the cells to injurious insults was increased after knockdown of Sirt6 expression. In contrast, YAMC cells with Sirt6 overexpression exhibited more resistance to injurious insult. Furthermore, intestinal epithelial-specific Sirt6 (Sirt6IEC-KO) knockout mice exhibited greater susceptibility to dextran sulfate sodium (DSS)-induced colitis. RNA sequencing transcriptome analysis revealed that inflammatory mediators such as tumor necrosis factor (TNF)-α suppressed expression of R-spondin-1 (Rspo1, a critical growth factor for intestinal epithelial cells) in Sirt6-silenced YAMC cells in vitro. In addition, lipopolysaccharide was found to inhibit colonic Rspo1 expression in Sirt6IEC-KO mice but not their control littermates. Furthermore, Sirt6IEC-KO mice with DSS-induced colitis also exhibited in a significant decrease in Rspo1 expression in colons. In vitro, knockdown of Rspo1 attenuated the effect of ectopic expression of Sirt6 on protection of YAMC cells against cell death challenges. In conclusion, Sirt6 plays an important role in protecting intestinal epithelial cells against inflammatory injury in a mechanism associated with preserving Rspo1 levels in the cells.